SIMULATOR PENYEDIA LAYANAN APLIKASI LOCATION BASED SERVICE PADA SISTEM LOCATION PLATFORM - Soegandi, Andreas (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Location based service using positioning system technology, known as Location Based Service (LBS), is the newest cellular technology that is commonly used service based on SMS. The purpose of this research is to make a software in form of LBS application service provider simulator that can help to develop the LBS application, especially in Location Platform system. The result is a software application that can be used in LBS application development without disturbing the running system application performance, support the productivity, and can be used as simulation to see the LBS application result.